PERAN KIAI DALAM MENANAMKAN NILAI KEJUJURAN PADA SANTRI DI PONDOK PESANTREN ROUDLOTUL MUHSINAT ALMAQBUL BULULAWANG MALANG - Yugi Carol Pratiwi; Abdul Jalil; Dian Muhammad Hakim (VICRATINA, 2021)
In this study, there are several objectives, including to describe the role of the kiai in instilling the value of honesty at the Roudlotul Muhsinat Al-Maqbul Islamic Boarding School Bululawang Malang, to describe how to instill the value of honesty in students at the Roudlotul Muhsinat Al-Maqbul Islamic Boarding School Bululawang Malang, to describe the inhibiting factors. and supporters in instilling the value of honesty in the students of the Roudlotul Muhsinat Al-Maqbul Islamic Boarding School Bululawang Malang. This research uses qualitative research and case study research. Data collection techniques used in this study were observation, interviews, and documentation. while the data analysis technique in this study used qualitative analysis to examine the results of the study, data condensation, data presentation, and data verification. The results of this study are the role of kiai in instilling the value of honesty in students including kiai as caregivers, kiai as motivators, kiai as second parents, and instilling the value of honesty in the roudlotul muhsinat Islamic boarding school using several steps such as the process of understanding honesty itself, exemplary, open, and don't overreact. The supporting factors are religious islamic boarding school activities, supportive rules, the cohesiveness of caregivers and administrators, adequate facilities and infrastructure, while the inhibiting factors are: heterogeneous number of students, awareness of caregivers, awareness of students to be honest.